The Analysis of Mathematical Literacy Skill and Respect to Local Culture toward Pogil Learning with Ethnomathematics - Fakhruddin, Deni Fikri; Masrukan, Masrukan (Universitas Negeri Semarang, 2018)
The objective of this study is to determine the effectiveness of POGIL learning with ethnomathematics towards students’ mathematical literacy skills. The population in this study were X graders students of State Senior High School 6 Cirebon in the academic year of 2015/2016. This study used quantitative methods. The sample was chosen by random sampling and it was obtained the class of X 1 as a control class with conventional learning and X 2 as an experiment class with POGIL model learning with ethnomathematics. The data collection methods were tests of mathematical literacy skills. The data analysis used was completeness test and average difference test. The results show that (1) the average mathematical literacy skill in POGIL learning with ethnomathematics has achieved classical completeness, it is at least 75% of students achieve a minimum score of 70; (2) the average class of mathematics literacy ability in POGIL learning with ethnomathematics is better than conventional learning class. From these results, it is said that POGIL learning with ethnomathematics is effective.